Dj, Toca O Som!" Entre A Produção De Festas E Subjetividades Na Cena Pop Lgbt De São Paulo - Almeida, Diego Eugenio Roquette Godoy [UNIFESP] (2018)
This Research Explores The Production Of Gender In The Nocturnal Leisure Of The City Of São Paulo. The Method Of Investigation Was The Participant Observation In Five Parties Created And Frequented By Young People That Make Up A Determined Pop Scene Lgbt, Pointing Out Possible Generational Differences Related To Masculine Homosexuality. The Musical Scene As A Theoretical And Methodological Delimitation For The Nighttime Leisure Has Undergone Modifications Based On Avtar Brah Intersectional Approach, Resulting In A Coherent Analytical Framework Regarding The Understanding Of Homosexuality. The Characteristics Of The Boundaries In The Investigated Scene Were: Age / Generation, Social Network Formed By Night People, Gender / Sex, And Musical Style. Five Parties Entered The Scope Of The Research: Hangover, Ratchet, Bug, The People And Plástika. They Occurred In Different Establishments In The City Of São Paulo, Three In The Region Of Augusta And Two In Barra Funda. I Stayed In Field About 100 Hours From December